Hawthorn (Crataegus spp.): an updated overview on its beneficial properties - Nazhand, Amirhossein (2020)
Medicinal plants, many of which are wild, have recently been under the spotlight worldwide due to growing requests for natural and sustainable eco-compatible remedies for pathological conditions with beneficial health effects that are able to support/supplement a daily diet or to support and/or replace conventional pharmacological therapy. The main requests for these products are: safety, minimum adverse unwanted effects, better efficacy, greater bioavailability, and lower cost when compared with synthetic medications available on the market. One of these popular herbs is hawthorn (Crataegus spp.), belonging to the Rosaceae family, with about 280 species present in Europe, North Africa, West Asia, and North America. Various parts of this herb, including the berries, flowers, and leaves, are rich in nutrients and beneficial bioactive compounds. Its chemical composition has been reported to have many health benefits, including medicinal and nutraceutical properties. Accordingly, the present review gives a snapshot of the in vitro and in vivo therapeutic potential of this herb on human health.